Strategi Komunikasi Pemasaran Pariwisata Danau Toba Oleh Badan Pelaksana Otorita Danau TOba (BPODT) Dalam Pengembangan Branding â€œLAKE TOBA CALDERA OF KINGSâ€ - Sagala, Wiranda Tappang (Komunika, 2023)
This research was conducted to analyze the marketing communication strategy of Lake Toba tourism and the obstacles of the Lake Toba Authority (BPODT) in developing the "Lake Toba Caldera of Kings" branding. The research method used is a descriptive method with a qualitative approach. The subjects in this study were two BPODT teams from the Public Communication and Marketing Division, while the triangulation informants were business people, community leaders and tourists. The results obtained are BPODT's communication strategy in developing Lake Toba branding through mass media such as: television, print media through newspapers and newspapers, booklets and new media by using social media sites and websites, such as Instagram, Twitter, Facebook, Youtube and Tiktok. BPODT has built new destinations in the authoritative zone, namely The Kaldera Nomadic Escape and the coordinative zone, namely the Tigarihit Colorful Village Tourism Village in Parapat. BPODT's obstacles in promoting Lake Toba tourism are the lack of tourism human resources both in quantity and quality, the lack of community roles in maintaining cleanliness, hospitality, and innovation in creating tourism products. While the infrastructure, there are still many road accesses to several Lake Toba attractions that are not feasible. Internet access and transportation are still inadequate and there is a lack of new tourist attractions in the Lake Toba area.